Tenure of Other People's Land without Rights (Case Study of Court Decisions No. 16/Pdt.G/2018/PN.Skh and No. 82/Pdt.G/2022/PN.Yyk) - Anjar Sari; Marisa Kurnianingsih (Proceeding International Conference Restructuring and Transforming Law, 2023)
Arbitrary land ownership is a crime where a person controls a plot of land without proof of ownership, but turns out to be the legal owner of the land in question.The research method used in this research is a normative juridical approach.This research approach is based on legal sources in the form of statutory regulations and court decisions related to control of land belonging to other people without rights. The research in this article is different from previous research which lies in the formulation of the problem raised and the location of the case. Regarding the regulation of control over land belonging to other people without rights, from the perspective of Islamic law, land that already has ownership rights is prohibited from being contested by anyone without the owner's consent.